Advection–Diffusion Modelling of Larval Capelin ( Mallotus villosus ) Dispersion in Conception Bay, Newfoundland - deYoung, Brad; Anderson, John; Greatbatch, Richard J.; Fardy, Paul (Canadian Journal of Fisheries and Aquatic Sciences, 1994)
A numerical model was used to determine the residence time of capelin (Mallotus villosus) larvae in Conception Bay, Newfoundland. The larvae were observed in the surface mixed layer of the Bay following release from beaches in June–July in order to examine how they move outside the Bay and what physical factors influence their rate of transport. A diagnostic model of Conception Bay provides a fixed velocity field which drives an advection–diffusion model applied to capelin larval dispersal from the Bay. The model was run for different periods to explore dependence of the residence time on different conditions during the period 1989–90. Model results showed that the residence time depends on the release location of the larvae in the Bay. While the residence time of the larvae does vary, we estimate it to be roughly 30 d for larvae released from the head of the Bay. Residence times are much shorter for larvae near the mouth of the Bay.